Urges to Move and Other Motivation States for Physical Activity in Clinical and Healthy Populations: A Scoping Review Protocol - Stults-Kolehmainen, Matthew A.; Blacutt, Miguel; Bartholomew, John B.; Boullosa, Daniel; Janata, Petr; Koo, Brian B.; McKee, Paul C.; Casper, Regina; Budnick, Christopher J.; Gilson, Todd A.; Blakemore, Rebekah L.; Filgueiras, Alberto; et al. (Frontiers in Psychology, 2022)
Motivation for bodily movement, physical activity and exercise varies from moment to moment. These motivation states may be “affectively-charged”, ranging from instances of lower tension (e.g., desires, wants) to higher tension (e.g., cravings and urges). Currently, it is not known how often these states have been investigated in clinical populations (e.g., eating disorders, exercise dependence /addiction, Restless Legs Syndrome, diabetes, obesity) versus healthy populations (e.g., in studies of motor control; groove in music psychology). The objective of this scoping review protocol is to quantify the literature on motivation states, to determine what topical areas are represented in investigations of clinical and healthy populations, and to discover pertinent details, such as instrumentation, terminology, theories and conceptual models, correlates and mechanisms of action. Iterative searches of scholarly databases will take place to determine which combination of search terms (e.g., “motivation states” and “physical activity”; “desire to be physically active”, etc.) captures the greatest number of relevant results. Studies will be included if motivation states for movement (e.g., desires, urges) are specifically measured or addressed. Studies will be excluded if referring to motivation as a trait. A charting data form was developed to scan all relevant documents for later data extraction. The primary outcome is simply the extent of the literature on the topic. Results will be stratified by population/condition. This scoping review will unify a diverse literature, which may result in the creation of unique models or paradigms that can be utilized to better understand motivation for bodily movement and exercise.